Elements for a Theory of Contemporary Mexican City from Urban Practice (Andamios, Revista de Investigación Social, 2013)
From studying the practice of urbanism in Mexico, it is often recognized the weakness or lack of theoretical propositions which in a coherent fashion, give support to decision makers process of conformation and continuous evolution of our cities’ spatial dimension.  Firstly, in this document, we will carry out a brief summary about the ideas usually related in teaching urbanism, between indigenous, colonial, Don Porfirio’s period and post-revolution (industrial) cities.  Secondly, we propose a comparison between theoretical and practical trends which define the fragments that give form to the Mexican contemporary city. From the stand point of the urban structure analysis of Mexico City and its metropolitan area we identify four dynamics which generated well differentiated spaces, mainly in terms of urban tissue, landscape, activities and social practices, which we use to call rationalists, residential, historic and popular.
Keywords: Urbanism; Urban Planning; History; Theory; Mexico City